Transformative blockchain technological approaches to sports events - Principe, Vitor; Ribeiro, Tiago; López-Carril, Samuel (Frontiers in Sports and Active Living, 2025)
The integration of blockchain technology in sports event management represents a significant shift towards more decentralized and efficient governance structures, particularly relevant to small and medium-sized events. Despite growing interest, its practical implementation remains limited and lacks comprehensive theoretical guidance. This study addresses this gap by proposing an integrated theoretical framework, combining the Dynamic Capabilities Framework (DCF), Collaborative Governance Theory (CGT), and the Four Modes of Governance (FMG), to systematically explore blockchain's application within sports event management. Our analysis reveals that blockchain technology can effectively foster transparency, efficiency, and enhanced stakeholder participation through Decentralized Autonomous Organizations (DAOs). These advantages are realized through key mechanisms of access, control, and incentives, which interact across external environments, governance structures, and blockchain core infrastructure. Furthermore, the study identifies critical managerial implications necessary for successful blockchain implementation, emphasizing strategic infrastructure assessments, stakeholder engagement, and risk management protocols. Ultimately, this research contributes both theoretical insights and practical guidelines, addressing existing knowledge gaps and providing a structured framework for leveraging blockchain in managing small to mediumsized sports events.